2002
DOI: 10.1515/hf.2002.045
|View full text |Cite
|
Sign up to set email alerts
|

Softwood Bark Pyrolysis Oil-PF Resols. Part 2. Thermal Analysis by DSC and TG

Abstract: ResolSoftwood bark Pyrolysis oil DSC TG Cure behavior of resins formulated with petroleum phenol replaced by 25 and 50 wt % of softwood bark-derived pyrolysis oils, using various formaldehyde to phenolics molar ratios and alkalinity content, was characterized by Differential Scanning Calorimetry (DSC). Kinetic parameters were obtained by the Borchart-Daniels method and the model-free (Vyazovkin) method. Resins containing up to 50 % by wt of pyrolysis oils had slower cure kinetics and lower extent of condensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…The DSC curves of PF resin and the control oil-PF resin present an exothermic peak with a maximum between 146 and 151 C, which indicated that they presented a similar curing process. This 840 D. Fan et al peak was associated with the condensation of methylol groups with phenolic units according to previous reports [9,18]. It is clearly seen from Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The DSC curves of PF resin and the control oil-PF resin present an exothermic peak with a maximum between 146 and 151 C, which indicated that they presented a similar curing process. This 840 D. Fan et al peak was associated with the condensation of methylol groups with phenolic units according to previous reports [9,18]. It is clearly seen from Fig.…”
Section: Resultssupporting
confidence: 73%
“…These resins showed nearly as well in making three-ply plywood of southern pine as a commercial resin. Oil-PF resols can be also prepared at phenol replacements of 25 and 50 wt% using bark-derived oils [6,9]. Strandboards manufactured with these resins exhibited comparable mechanical properties with those of panels made with commercial surface resins under the same pressing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted on resins containing pyrolytic oil yielded E a ranging between 119 and 149 kJ/mol for various formulations of PF‐pyrolytic oil resins containing 50% of phenol substitution 14. These values were obtained through differential scanning calorimetry (DSC), and both the pyrolytic oil and PF‐resins were different from those used here.…”
Section: Resultsmentioning
confidence: 75%
“…Many of the components of the pyrolytic oil are related to phenol and aldehydes and can react with the PF resin 7, 8, 31, 32. However, some of these constituents will also dilute the blend and interfere with the reacting molecules, thus increasing gel time 14. This dilution effect and reaction competition could explain slower gelling process.…”
Section: Resultsmentioning
confidence: 99%
“…Furfural and furfuryl alcohol are present at up to 30 and 12-30%, respectively. Phenol-formaldehyde resins have been prepared from bio-oils containing a high fraction of phenolic compounds [10,11]. Although bio-oils are presently of interest for heat and power generation, their use as a source of chemicals may become attractive in future.…”
Section: From Biomass To Products Via Degraded Moleculesmentioning
confidence: 99%